Uma investigação sobre o papel do interlocutor de libras como mediador em aulas de física para alunos com deficiência auditiva - Almeida, Thiago Jose Batista de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The research reported is in the physics teaching for hearing impaired studentes mediated by an Brazilian sing language (LIBRAS) interlocutor. The interaction researched were: (a) interpreter /deaf student; (b) Teacher/deaf student and hearing student/deaf student. It is understood that mediation can be related with two aspects: the physics component and the indirect actions related with the contempt as class organization to methodological procedures. This is qualitative research, filming of the interpretation from Portuguese into LIBRAS was used as a source for data. Those filming were made through six classes and the interpretation was done by the interpreter, in which there were discussed the main topics that involves concepts of heat and temperature. To understand what was interpreted by the interpreter, it was made, by a Libras teacher and interpreter, the transcription of that into Portuguese. It was also done a semi organized interview with the interpreter in order to complement the data of the research. The information obtained in the film shows that, in some moments, there are similarities and in others there are differences between the speech of the teacher and the translation made by the interpreter. According to our analysis, the differences were related to three factors: 1. Shor time of experience of the interpreter, who had gotten a little expressive vocabulary in LIBRAS, in due her formation in LIBRAS in a course of only 120 hours; 2. Difficulties in the interpretation of physics content, because of the interpreter formation in languages and not physics; 3. Lack of sings for researched physics content in LIBRAS. We concluded that the mediation of physics content in LIBRAS. We concluded that the mediation of physics content wasn't satisfactory, above all in due those points cited above

A investigação relatada se insere no contexto do ensino de física para alunos surdos mediado por interlocutor de Língua Brasileira de Sinais - LIBRAS. As interações investigadas foram: (a) interlocutor/aluno surdo; (b) docente/aluno surdo e (c) aluno ouvinte/surdo. Entende-se que a mediação pode se dar em torno de dois aspectos: o conteúdo de Física e as ações indiretas em relação ao conteúdo, tais como a organização da sala para procedimentos metodológicos. A presente pesquisa, de natureza qualitativa, utilizou como fonte de dados a filmagem da interpretação da Língua Portuguesa para a LIBRAS, realizada pela interlocutora em seis aulas, onde foram discutidos os principais tópicos que envolvem os conceitos de calor e de temperatura. A fim de compreender o que interpretado pela interlocutora, foi realizada a transcrição de sua interpretação para a Língua Portuguesa, estabelecida por uma professora intérprete de LIBRAS. Foi realizada também uma entrevista semiestruturada com a interlocutora, visando complementar os dados da pesquisa. As informações obtidas na filmagem indica que, em alguns momentos, há semelhanças, e em outros, diferenças entre a fala da professora e a tradução realizada pela interlocutora. Segundo nossa análise, as diferenças estão relacionadas a três fatores: 1. Pouco tempo de atuação da interlocutora, que possuía um vocabulário em LIBRAS ainda pouco expressivo, devida a sua formação em LIBRAS corresponder a um curso de 120 horas; 2. Dificuldade na interprestação dos conteúdos físicos, devido à interlocutora ter formação acadêmica em Letras e não em Física; 3. Ausência de sinais em LIBRAS dos conceitos físicos investigados. Conclui-se, dessa forma, que a mediação dos conteúdos físicos não foi satisfatória, sobretudo em função desses três pontos citados
Keywords: Fisica; Ensino; Calor; Temperatura; Alunos; Deficientes auditivos; Língua brasileira de sinais; Tradutores; Physics